Scientific Astrophotography How Amateurs Can Generate and Use Professional Imaging Data - Hubbell, Gerald R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Scientific Astrophotography is a work for those amateur astronomers looking for new challenges, once they have mastered visual observing and the basic imaging of various astronomical objects. It is a wonderful reference for scientifically-inclined observers who want to learn the fundamentals of astrophotography with a firm emphasis on the discipline of scientific imaging. This book is a wealth of information and a distillation of ideas presented by a diverse set of sources and based on the most recent techniques, equipment, and data available. It also includes numerous exercises for the reader, to maximize the success and minimize the frustration inherent in the pursuit of this specific craft. Scientific Astrophotography is perfect for any amateur astronomer who wants to go beyond just the process of making beautiful images and actually contribute to the science of astronomy! "...Gerald Hubbell's new book, Scientific Astrophotography, is the perfect companion for anyone dipping their toe into the digital imaging realm for the first time. The author answers all the questions people have when starting out, such as how do I get the most bang for my buck, and how do I select the right CCD for my telescope?" - Mike Simonsen, American Association of Variable Star Observers
Foreword -- Acknowledgements -- About the Author -- Table of Contents -- List of Figures -- List of Tables -- Preface -- Chapter 1: Introduction to Scientific Astrophotography -- PART I: Astronomical Imaging System (AIS) -- Chapter 2: The "Perfect AIS" -- Chapter 3: The Astrograph - The Imaging Telescope -- Chapter 4: CCD Chip Performance, CCD Camera Basics, and Image Scaling Factors -- Chapter 5: Telescope Mount Factors -- Chapter 6: Imaging Filters and Auxiliary Optical/Mechanical/Electrical Components -- Chapter 7: Astrograph and CCD Combinations -- Chapter 8: Environmental and External Factors -- PART II: Astronomical Imaging System (AIS) Integration and Operation -- Chapter 9: The Practical AIS - The Sum is Greater than the Parts -- Chapter 10: Planning and Executing the AIS Data Acquisition Process -- Chapter 11: Image Acquisition and Calibration -- Chapter 12: Field Practical Exercises (FPE) - Putting It All Together -- PART III: Scientific Image Data Analysis and Advanced Amateur Scientific Projects -- Chapter 13: Scientific Image Data Uses and Innovations in AIS Components and Systems -- Chapter 14: An Introduction to Scientific Image Data Analysis -- Chapter 15: Your Scientific Imaging Program and How to Submit Your Data to Scientific Organizations -- Chapter 16: Amateur Astronomer Access to Professional-Level Observatories -- Appendices -- Index.
Keywords: Physics; Computer vision; Astronomy; Photography, artistic; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Image Processing and Computer Vision; Photography